The Role of BDNF on Neural Plasticity in Depression - Yang, Tao; Nie, Zheng; Shu, Haifeng; Kuang, Yongqin; Chen, Xin; Cheng, Jingmin; Yu, Sixun; Liu, Huiying (Frontiers in Cellular Neuroscience, 2020)
Using behavioral, pharmacological, and molecular methods, lots of studies reveal that depression is closely related to the abnormal neural plasticity processes occurring in the prefrontal cortex and limbic system such as the hippocampus and amygdala. Meanwhile, functions of the brain-derived neurotrophic factor (BDNF) and the other neurotrophins in the pathogenesis of depression are well known. The maladaptive neuroplastic in depression may be related to alterations in the levels of neurotrophic factors, which play a central role in plasticity. Enhancement of neurotrophic factors signaling has great potential in therapy for depression. This review highlights the relevance of neurotrophic factors mediated neural plasticity and pathophysiology of depression. These studies reviewed here may suggest new possible targets for antidepressant drugs such as neurotrophins, their receptors, and relevant signaling pathways, and agents facilitating the activation of gene expression and increasing the transcription of neurotrophic factors in the brain.